2016
DOI: 10.18438/b8t922
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Online Information Literacy Learning Objects For First Year Community College English Composition

Abstract: Objective -The main objective was to determine whether information literacy (IL) learning objects (LOs) impact student IL competency, specifically in a foundational first year English composition course. The primary research question was: What is the effectiveness of IL LOs compared to face-to-face instruction in terms of students' skill acquisition?Methods -The methods involved testing student IL competency through a multiple-choice test given pre-and post-IL intervention. Effectiveness was measured by assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Of the remaining seven studies, three were based in the U.K. (Brettle & Raynor, 2013;Walton & Hepworth, 2012;Swain et al, 2015 unpub. ), two in Australia (Churkovich & Oughtred, 2002;Salisbury & Ellis, 2003), one in Canada (Bordignon et al, 2016) and one in the Czech Republic (Kratochvil, 2014).…”
Section: Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Of the remaining seven studies, three were based in the U.K. (Brettle & Raynor, 2013;Walton & Hepworth, 2012;Swain et al, 2015 unpub. ), two in Australia (Churkovich & Oughtred, 2002;Salisbury & Ellis, 2003), one in Canada (Bordignon et al, 2016) and one in the Czech Republic (Kratochvil, 2014).…”
Section: Study Qualitymentioning
confidence: 99%
“…Only two studies carried out formal validity testing (Brettle & Raynor, 2013;Mery et al, 2012a) with a further five piloting the test before use (Bordignon et al 2016;Burhanna et al, 2008;Churkovich & Oughtred, 2002;Kratochvil, 2014;Swain et al, 2015 unpub.). Finally, one study used a predetermined rubric for marking (Goates et al, 2016).…”
Section: Study Qualitymentioning
confidence: 99%
“…These smaller sample sizes are of concern, especially when comparing multiple interventions, as their size often affects the study's power to detect statistical significance as well as external validity. Most recently in the literature, Bordignon et al (2016) conducted a controlled study comparing students' information literacy skills in response to online IL learning objects and face-to-face workshops. Their sample (N = 110) was comprised of 75 students during Spring semester and 35 students the subsequent Fall term.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In each of these cases, the dependent variables were skill-based outcomes (Anderson & May, 2010;Bordignon et al, 2016;Germain et al, 2000;Hess, 2014) or a combination of skill-based and affective measures (Churkovich & Oughtred, 2002;Kaplowitz & Contini, 1998). Other studies have more thoroughly investigated students' affective approaches, though not within the context of comparing online and in-person interventions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More studies can be found in the literature reporting on consistent findings of the use of Learning Objects in primary education [15]- [17], secondary education [15], [16], [18] and higher education [19]- [23]. It is also worth pointing out that some studies did not found significant difference between the performance of students taught using Learning Objects and those students taught with traditional methods [203]- [206]. Nevertheless, in general, these studies found that using Learning Objects is at least as effective as traditional learning.…”
Section: Use Of Learning Objects In Educational Environmentsmentioning
confidence: 99%